Analisis Stakeholder dalam Kebijakan Pemenuhan Fasilitas Kesehatan Tingkat Pertama pada Program Jaminan Kesehatan Nasional di Kabupaten Jember (Stakeholder Analysis in Compliance Policy of The First-Level Health Facilities in National Health Insurance at - Mohammad Alfian Yuliansyah; Nuryadi Nuryadi; Yennike Tri Herawati (Pustaka Kesehatan, 2016)
Decree of President No. 12 in 2013 explained that The Government and Local Government had a responsibility for availability of health facilities and implementation of health services in National Health Insurance. The first level-health facilities which had been collaborated with Social Assurance Agency in Health were 97. Based on ratio, the number of the first level-health facilities in Jember were less. The shortage was The government's resposibility based on Decree of President No. 12 in 2013.This research aims to analize of stakeholder policy in compliance policy of the first level-health facilities in National Health Insurance at Jember.This research was descriptive research with mixed methods approach. The result explained that Social Assurance Agency in Health of Jember needed to get cooperation with 230 doctors and 35 primary health care or clinics. Social Assurance Agency in Health of Jember had a big power to get cooperation with the first-level health facilities which be available in Jember during get a cooperation with doctors and available clinics also invite other investors to build a new clinics. The first level-health facilities, specially clinics and doctor had a rights to have cooperation or not with Social Assurance Agency in Health. Keywords: Policy, Stakeholder, The First-Level of Health Facilities, UHC